Detection of HER2+ Breast Cancer Cells using Bioinspired DNA‐Based Signal Amplification. (16th January 2020) - Rafiee, Sarah D.; Kocabey, Samet; Mayer, Michael; List, Jonathan; Rüegg, Curzio
Abstract: Circulating tumor cells (CTC) are promising biomarkers for metastatic cancer detection and monitoring progression. However, detection of CTCs remains challenging due to their low frequency and heterogeneity. Herein, we report a bioinspired approach to detect individual cancer cells, based on a signal amplification cascade using a programmable DNA hybridization chain reaction (HCR) circuit. We applied this approach to detect HER2 + cancer cells using the anti‐HER2 antibody (trastuzumab) coupled to initiator DNA eliciting a HCR cascade that leads to a fluorescent signal at the cell surface. At 4 °C, this HCR detection scheme resulted in highly efficient, specific and sensitive signal amplification of the DNA hairpins specifically on the membrane of the HER2 + cells in a background of HER2 − cells and peripheral blood leukocytes, which remained almost non‐fluorescent. The results indicate that this system offers a new strategy that may be further developed toward an in vitro diagnostic platform for the sensitive and efficient detection of CTC. Abstract : Cancer cell detection via an amplified fluorescence signal: We developed a programmable DNA circuit system based on hybridization chain reaction (HCR); this is a bioinspired signal amplification approach that allows specific and sensitive detection of HER2 + breast cancer cells among HER2 − cells, including freshly isolated peripheral blood mononuclear cells.